BEHAVIOR OF MODEL GROUP PILES SUBJECTED TO LATERAL SOIL MOVEMENT IN SAND - Saad Farhan Ibraheem; Mohammed Khachi Hatem (Journal of Engineering and Sustainable Development, 2017)
Laboratory model tests have been carried out to explore the behavior of piles subjected to lateral soil movement in sand. The results of a single pile test and ten tests on of group piles arranged in a row (perpendicular to the direction of soil movement) are presented. Different parameters were utilized in these tests, (e.g., pile spacing, number of piles within a group and pile head condition). Group effect was calculated using group factor (Fm) which is defined in terms of the measured maximum bending moments of an individual with group and that of the single pile. The results showed that the maximum bending moment of group piles decreases from the single pile with decreasing pile spacing and the pile behaves essentially the same as a single pile when the pile spacing is 7d or more. The maximum reduction of the maximum bending moments of about (17%) and (28%) as compared with that for the standard single pile may be observed for a pile spacing of 3d for the free and capped headed condition, respectively.